Therapeutic Landscape of Malignant Pleural Mesothelioma: Collateral Vulnerabilities and Evolutionary Dependencies in the Spotlight - Xu, Duo; Yang, Haitang; Schmid, Ralph A.; Peng, Ren-Wang (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is the epitome of a recalcitrant cancer driven by pharmacologically intractable tumor suppressor proteins. A significant but largely unmet challenge in the field is the translation of genetic information on alterations in tumor suppressor genes (TSGs) into effective cancer-specific therapies. The notion that abnormal tumor genome subverts physiological cellular processes, which creates collateral vulnerabilities contextually related to specific genetic alterations, offers a promising strategy to target TSG-driven MPM. Moreover, emerging evidence has increasingly appreciated the therapeutic potential of genetic and pharmacological dependencies acquired en route to cancer development and drug resistance. Here, we review the most recent progress on vulnerabilities co-selected by functional loss of major TSGs and dependencies evolving out of cancer development and resistance to cisplatin based chemotherapy, the only first-line regimen approved by the US Food and Drug Administration (FDA). Finally, we highlight CRISPR-based functional genomics that has emerged as a powerful platform for cancer drug discovery in MPM. The repertoire of MPM-specific “Achilles heel” rises on the horizon, which holds the promise to elucidate therapeutic landscape and may promote precision oncology for MPM.